Case Study : Observation of Reducing Heartburn Pain in Gastroesophageal Reflux Disease (Gerd) With Hypnotherapy - Hutomo, Yudhistira (Syntax Corporation Indonesia, 2024)
Hypnotherapy is a form of psychological treatment that utilizes hypnosis to assist in addressing specific mental and physical ailments. It can also be employed for altering habits. Hypnotherapy operates by inducing a hypnotic state in the subject, lowering brain waves to alpha-theta levels for relaxation and enhanced acceptance of suggestions in the subconscious. The aim is to improve psychological issues, emotions, and conduct. The study was carried out on two patients at the Lee Chen Thung Primary Clinic in Jakarta, Indonesia. Sampling was conducted by adhering to specific criteria for selection and administering the GERD-Q questionnaire. The patients included in the study had to have GERD-Q scores higher than 7 and frequently use PPIs for their stomach issues. Management of GERD can be done with drug therapy or pharmacology and non-pharmacology therapy. One of the non-pharmacology therapies that can be given is hypnotherapy. Patients who satisfied the criteria were provided with hypnotherapy in order to alleviate their heartburn symptoms. The process of hypnotherapy can help the body to stimulate the release of endorphins. Endorphins act as the body's innate pain relievers. Following hypnotherapy, patients underwent eval_uation for 1 week using numeric rating scale. Both patients experienced a decrease in pain levels following hypnotherapy.